الکتب التى صادرتها محاکم التفتیش فى اوربا 1834 – 385 میلادیة : دراسة تاریخیة ببلیومتریة - د. محمد خمیس الحباطى (المجلة الدولية لعلوم المكتبات والمعلومات)
A study aimed at dealing with books confiscated by the Inquisition inEurope, This is by drawing on the historical method, to determine the impact ofthe intellectual renaissance on the Church in Europe, In addition, the Inquisitionwas dealt with in terms of its concept, origin, composition, and Places of itsspread, As well as using the method of bibliographic research to determine thegeneral features of books confiscated by the Inquisition in Europe, In addition todefining the role of the Inquisition in controlling intellectual production, As well aslearn about lists of prohibited books, The fate of the Inquisition, The resultsindicated that the Inquisition paralyzed the scientific movement of the entirenation, Also, the books confiscated by the Inquisition amounted to 209 books for(137) authors during the period from the twelfth century until the twentieth centuryA.D. in various subjects, including: Religious writings and books that offend publicmodesty, and political writings focused on freedoms, Philosophical writings,literary and artistic writings in poetry, music, novels and plays, In addition to theproliferation of the Inquisition in various places in Europe, such as: Spain 1478,France 1329, Portugal 1547, and in Italy in the late sixteenth century CE inAquileia, Naples and Venice, Also in Andalusia, beginning in 1501 CE, when thedecree issued to burn all Islamic books was issued.